2010
DOI: 10.1002/agr.20227
|View full text |Cite
|
Sign up to set email alerts
|

Household demand analysis of organic and conventional fluid milk in the United States based on the 2004 Nielsen Homescan panel

Abstract: Using the 2004 AC Nielsen panel consisting of over 38,000 households, the authors ascertain the influence of selected demographic variables associated with the purchase of organic fluid milk through the estimation of a probit model. From the use of the Heckman two-step procedure, they also calculate own-price, cross-price, and income elasticities by estimating demand relationships for both organic and conventional milk. They find that demographic factors play a crucial role in the household choice of purchasin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
47
2
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 13 publications
11
47
2
3
Order By: Relevance
“…The impact of income is higher on OB milk than on OPL milk. These findings are in line with results of prior studies for the United States (e.g., Alviola & Capps, ; Dettmann & Dimitri, ; Zhang, Huang, Lin, & Epperson, ) and for Germany (Jonas & Roosen, ).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The impact of income is higher on OB milk than on OPL milk. These findings are in line with results of prior studies for the United States (e.g., Alviola & Capps, ; Dettmann & Dimitri, ; Zhang, Huang, Lin, & Epperson, ) and for Germany (Jonas & Roosen, ).…”
Section: Resultssupporting
confidence: 92%
“…Dhar and Foltz () who applied a quadratic AIDS (Q‐AIDS) found own‐price elasticities for conventional and organic milk to be −1.0 and −1.4, respectively. Alviola and Capps () presented own‐price elasticity estimates of −0.87 for conventional milk and of −2.0 for organic milk. Choi and Wohlgenant () analyzed the U.S. milk market at a disaggregated level.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…This information, along with the date of purchase, is linked with demographic details of the household and the household purchasing history. j Outside the wine sector, Homescan data have also been used to estimate brand level price elasticities and price response elasticities (Cotterill, 1994), change in household purchasing habits due to business cycle fluctuation (Cotti et al, 2014), the influence of selected demographic variables associated with purchase of organic milk (Alviola and Capps, 2010), the effect of taxes on sales (Harding et al, 2012) and the causes of price difference across households (Abe and Shiotani, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Less numerous are the papers in which the profile is obtained using actual sales data (e.g. Prasad et al, 2008;Zhang et al, 2008;Alviola and Capps, 2010;Brouhle and Khanna, 2012). Previous studies have found that there is a gap between attitudes and purchase (Kim and Damhorst, 1998;Carrigan andAtalla, 2001, Nicholls andLee, 2006;De Pelsmacker and Janssens, 2007).…”
Section: Introductionmentioning
confidence: 99%